Does shoe collar height influence ankle joint kinematics and kinetics in sagittal plane maneuvers? - Yang, Y.; Fang, Y.; Zhang, X.; He, J.; Fu, W. (Journal of Sports Science & Medicine, 2017)
The Objective of the study is to investigate the effects of basketball shoes with different collar heights on ankle kinematics and kinetics and athletic performance in different sagittal plane maneuvers. Twelve participants who wore high-top and low-top basketball shoes (hereafter, HS and LS, respectively) performed a weight-bearing dorsiflexion (WB-DF) maneuver, drop jumps (DJs), and lay-up jumps (LJs). Their sagittal plane kinematics and ground reaction forces were recorded using the Vicon motion capture system and Kistler force plates simultaneously. Moreover, ankle dorsiflexion and plantarflexion angles, moment, power, stiffness, and jump height were calculated. In the WB-DF test, the peak ankle dorsiflexion angle (p = 0.041) was significantly smaller in HS than in LS. Additionally, the peak ankle plantarflexion moment (p = 0.028) and power (p = 0.022) were significantly lower in HS than in LS during LJs but not during DJs. In both jumping maneuvers, no significant differences were found in the jump height or ankle kinematics between the two shoe types. According to the WB-DF test, increasing shoe collar height can effectively reduce the ankle range of motion in the sagittal plane. Although the HS did not restrict the flexion-extension performance of the ankle joint during two jumping maneuvers, an increased shoe collar height can reduce peak ankle plantarflexion moment and peak power during the push-off phase in LJs. Therefore, a higher shoe collar height should be used to circumvent effects on the partial kinetics of the ankle joint in the sagittal plane.